Effect of filtration rate on coal-sand dual-media filter performances for microalgae removal. Issue 3 (1st February 2017) - Sabiri, Nour-Eddine; Monnier, Elodie; Raimbault, Virginie; Massé, Anthony; Séchet, Véronique; Jaouen, Pascal
ABSTRACT: This study tested the efficiency of granular filtration using a bilayer sand filter for microalgae removal from culture dilutions ranging from 10, 000 to 17, 000 cells/mL. The objective is to evaluate the removal capacity of the filter without chemical coagulation. Two filter media, sand and anthracite, with mean grain sizes of 0.395 and 1.2 mm, respectively, were used in constant-flow-rate experiments (down-flow mode) with suspensions containing Heterocapsa triquetra microalga. The conventional rapid filtration which usually operates at a constant rate of approximately 5 m 3 /m 2  h is compared to high-rate filtration. Two filtration velocities (5 and 10 m/h) were investigated with bed depth of 1100 mm. Average microalgal cell removal rates were 90% at 5 m/h and 68% at 10 m/h. Turbidity removal was more than 71% at 5 m/h but just 57% at 10 m/h. Head losses did not increase significantly, and values measured at process end were 32 mbar at 5 m/h and 78 mbar at 10 m/h. Retention probabilities were calculated from experimental data. A theoretical model was used to evaluate the contributions of the different drivers of microalgae removal. Hypotheses are developed on the understanding of change in the mechanisms of retention as a function of filtration velocity.